2003
DOI: 10.1194/jlr.r300013-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic lipid signaling

Abstract: Neuronal cellular and intracellular membranes are rich in specialized phospholipids that are reservoirs of lipid messengers released by specific phospholipases and stimulated by neurotransmitters, neurotrophic factors, cytokines, membrane depolarization, ion channel activation, etc. Secretory phospholipases A 2 may be both intercellular messengers and generators of lipid messengers. The highly networked nervous system includes cells (e.g., astrocytes, oligodendrocytes, microglial cells, endothelial microvascul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
47
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(50 citation statements)
references
References 139 publications
2
47
1
Order By: Relevance
“…Polyunsaturated fatty acids and N-acyl ethanolamides are signaling molecules implicated in a multitude of physiological and pathophysiological events, including cardiac and neuronal excitability (31,33,40,42), cardioprotection and neuroprotection from ischemic and epileptic episodes (31, 34 -36, 40), inflammation, and pain (32,39). Considering the role of T-channels in cardiac and neuronal pacemaker (1, 2, 13, 14), cardiac hypertrophy (15), neuroprotection, and absence epilepsy (8,9,67) as well as in pain perception (10 -12), it is attractive to suggest that T-channel inhibition may contribute to polyunsaturated fatty acid and N-acyl ethanolamide effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polyunsaturated fatty acids and N-acyl ethanolamides are signaling molecules implicated in a multitude of physiological and pathophysiological events, including cardiac and neuronal excitability (31,33,40,42), cardioprotection and neuroprotection from ischemic and epileptic episodes (31, 34 -36, 40), inflammation, and pain (32,39). Considering the role of T-channels in cardiac and neuronal pacemaker (1, 2, 13, 14), cardiac hypertrophy (15), neuroprotection, and absence epilepsy (8,9,67) as well as in pain perception (10 -12), it is attractive to suggest that T-channel inhibition may contribute to polyunsaturated fatty acid and N-acyl ethanolamide effects.…”
Section: Discussionmentioning
confidence: 99%
“…Anandamide (N-arachidonoyl ethanolamide, AEA) 2 belongs to a new major class of small lipid messengers, including endocannabinoids and N-acyl-related molecules, eicosanoids, and fatty acids (22, 28 -32). These bio-active lipids are involved in a multitude of physiological and pathophysiological events, including neuronal excitability (22,23,31,33), sleep (34), epilepsy and neuroprotection (34 -37), inflammation and pain (28,29,32,38,39), as well as cardiovascular modulation (40 -42), fertilization, and cell cycle progression (38,43,44). Despite the fact that both small lipid messengers and T-channels display similar physiological functions (but with opposite effects), little is known about the properties and the specificity of this new class of molecules on the three Ca V 3 channels.…”
mentioning
confidence: 99%
“…Several genes have been reported to be activated by dietary long-chain PUFA, and some gene products, alone or in combination with the membrane effects of these PUFA, exert their beneficial effect on neural functions such as learning and memory. The fact that ALA and DHA activate several genes in other tissues, like liver or adipose tissue, is well known (40)(41)(42)(43)(44)(45), but the underlying molecular mechanisms of the direct effects of PUFA diet-induced gene-expression changes in the brain have been addressed by very few studies (46)(47)(48)(49)(50)(51)63).…”
Section: Effect Of Dietary Omega-3 Pufa On Gene Expression In the Brainmentioning
confidence: 99%
“…Several reports suggested that DHA may also prevent apoptosis in neurons (6). AA is believed to function directly as a signaling molecule and is a precursor of several eicosanoid molecules that also have signaling functions within the nervous system (7).…”
mentioning
confidence: 99%